Effects of enzyme supplementation and particle size of wheat-based diets on nursery and finishing pigs - Mavromichalis, I.; Kennedy, G.A.; Hines, Robert H.; Senne, B.W.; Sorrell, S.P.; Hancock, Joe D.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In nursery pigs, enzyme supplementation generally had no effect on ADG or F/G, but a trend occurred for greater digestibility of DM in pigs fed enzymes. However, one notable interaction occurred. Enzyme supplementation gave improved F/G at the coarser (l,300 mm) particle size but not at the finer (600 or 400 mm) particle sizes. In finishing pigs, trends for better F/G and digestibilities of DM and N with enzyme supplementation occurred in one experiment (1,300 vs 600 mm) but not in the other experiment (600 vs 400). Thus, the effects of enzyme supplementation were neither large nor consistent, but wheat particle sizes of 600 and 400 mm supported the best growth performances in nursery and finishing pigs, respectively.
Keywords: Swine; Nursery pigs; Finishing pigs; Wheat; Enzymes; Particle size